Physical Activity and Psychological Well-Being During the COVID-19 Lockdown: Relationships With Motivational Quality and Nature Contexts - Jenkins, Matthew; Houge Mackenzie, Susan; Hodge, Ken; Hargreaves, Elaine Anne; Calverley, Jessica R.; Lee, Craig (Frontiers in Sports and Active Living, 2021)
Physical activity, motivation, psychological well-being, nature, COVID-19.